2003
DOI: 10.1088/0268-1242/19/1/005
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of the photoluminescence emission from InAs quantum dots in a strained Ga0.85In0.15As quantum well

Abstract: Photoluminescence from InAs quantum dots in a strained Ga 0.85 In 0.15 As quantum well is investigated over a temperature range from 10 to 300 K using low intensity optical excitation. A rate equation model for the carrier dynamics is fitted to the experimental data obtained for the integrated intensity of the photoluminescence at different temperatures. It is found necessary to assume a potential barrier, possibly arising from the strain, at the interface between the dots and the quantum well that makes the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 29 publications
4
53
0
2
Order By: Relevance
“…This has been explained in terms of the dependence of carrier capture on the strain-induced potential barrier at the interface between the well and the dot. [24][25][26] Hence the precise nature of the strain fields in and around the QD plays a fundamental role in shaping the optical emission.…”
Section: Role Of Segregation In Inas/gaas Quantum Dot Structures Cappmentioning
confidence: 99%
“…This has been explained in terms of the dependence of carrier capture on the strain-induced potential barrier at the interface between the well and the dot. [24][25][26] Hence the precise nature of the strain fields in and around the QD plays a fundamental role in shaping the optical emission.…”
Section: Role Of Segregation In Inas/gaas Quantum Dot Structures Cappmentioning
confidence: 99%
“…This behavior has been already observed in similar structures and it has been justified by different hypotheses including resonant energy levels between different families, 40 losses of carriers from the WL to the GaAs, 26,36 losses within the barrier itself, 38,39 or losses related to defects. 8,11,37 With the exception of the structure with x ¼ 0.30, three regions can be distinguished in the temperature variation of the recombination time in all samples for QD1 (Fig.…”
Section: -2mentioning
confidence: 67%
“…The observed Arrhenius dependence would be accounted for by two activation energies, as commonly observed in similar QD structures. 26,[36][37][38][39] The sharp decrease of the PL intensity corresponds to a large activation energy (200-400 meV) that depends on the barrier composition (see Tables I and II); the energy difference is consistent with the thermionic electron-hole escape from QD to the WL/WL-QW (for UCL structures).…”
Section: -2mentioning
confidence: 78%
See 1 more Smart Citation
“…This is true, in particular, for the strong PL quenching which occurs within multi-atomic structures. Several studies have tried to improve the adjustment of experimentally observed temperature dependences developing different models [2,6].…”
Section: Introductionmentioning
confidence: 99%